Nutritional characterization of Trachurus lathami discarded by the Argentine fishing industry: first step towards the sustainable valorization of the species - Mitton, Francesca María (2024)
In the Argentine Continental Shelf pelagic fi sheries, rough scad (Trachurus lathami) is incidentally caught, being discarded by the commercial fl eet despite its high abundances. With the aim of promoting the sustainable use of this species, the nutritional characterization of T. lathami is reported here for the fi rst time. High protein (16%) and lipid (5.4%) content in whole individuals indicated that this is a moderately fat species. In the edible portion, within total lipids (4.8%), the n-3 polyunsaturated fraction was represented by docosahexaenoic (16.8%) and eicosapentaenoic (5.6%) acids. Results encourage potential strategies towards the developing of restructured products for human consumption.